Sufficiency Economy Philosophy and Buddhist Principles - Pimpachat, Nutthapong; Akkhachat, Manit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
The purposes of this research were: 1. To study the level of knowledge about Sufficiency Economy Philosophy of Undergraduate Students at the Faculty of Education, Nakhon Ratchasima Rajabhat University and 2. To study the level of understanding of Sufficiency Economy Philosophy and Buddhism Principles of undergraduate students from Faculty of Education, Nakhon Ratchasima Rajabhat University classified by gender. The samples of the research was 30 second-year students in undergraduate level from 17 majors in Faculty of Education, Nakhon Ratchasima Rajabhat University in the academic year 2020. The instrument used in this research was a questionnaire of knowledge and understanding. The quality of the tool was determined by content validity from 3 experts and the reliability value was 1.00. The statistics used in data analysis were percentage, mean, and standard deviation The results of the research were as follows: 1. Knowledge level about the philosophy of sufficiency economy of undergraduate students from Faculty of Education, Nakhon Ratchasima Rajabhat University was at high level (x̅= 8.77, S.D = 0.51). 2. Level of understanding About the Philosophy of Sufficiency Economy and the Principles of Buddhism of undergraduate students from Faculty of Education, Nakhon Ratchasima Rajabhat University was at high level (x̅ = 7.83, S.D = 1.15)